Awareness of opinion change: evidence from two deliberative mini-publics - Himmelroos, Staffan; Christensen, Henrik Serup (Frontiers in Political Science, 2024)
Although opinion changes during discussions and negotiations have been studied extensively in different fields of research, surprisingly little effort has been put into studying whether people correctly recognize that they revised their opinions. This is important because it has implications for both the cognitive mechanisms underpinning these changes and their likely consequences. We in this study examine whether participants in two deliberative mini-publics (DMP) were able to determine the extent to which they revised their opinions (DMP1 = 135; DMP2 = 207). We measure awareness with two questions asking respondents to indicate the extent to which their opinions and views changed during the processes, while we ascertain the actual developments with three measures that capture developments in opinions and attitude consistency. Our results suggest that people are generally unaware of revising their opinions during these processes, and it is only for drastic opinion changes that people have some level of awareness. The difference in how people perceive opinion change compared to how they respond to statements about policy issues shows that probing opinion changes by asking people directly about this can be problematic from a methodological standpoint.